Mothers Need Time-Outs, too : It's Good to be a Little Selfish : It Actually Makes you a Better Mother - Callahan, Susan ; Nolen, Anne and Schumann, Katrin (New York McGraw-Hill, 2008)
Intended for real women in the post-Supermom era, this book challenges the notion that good parents should be selfless. It presents insights of moms on how they used "time-out" sessions, stress-busters, and other ingenious techniques to become happier people, and better mothers
Include Index
Keywords: Mothers--Conduct of life -- Mothers--Psychology -- Pleasure